Effects of aripiprazole on insight and subjective experience in individuals with an at-risk mental state - Kobayashi, Hiroyuki; Morita, Keiko; Takeshi, Kiyoaki; Koshikawa, Hiroki; Yamazawa, Ryoko; Kashima, Haruo; Mizuno, Masafumi (Journal of clinical psychopharmacology, 2009)
Although medication with antipsychotic for the psychosis prodrome has often caused some ethical issues, recent studies have shown that some novel antipsychotics are safer and more tolerable for young people. This study aimed to investigate whether the administration of aripiprazole would not only relieve the prodromal symptoms but also be tolerable for prodromal subjects and to evaluate the effect of medication on improvements in insight and subjective well-being. The Structured Interview for Prodromal Syndromes was performed for patients identified as having the psychosis prodrome. Psychiatric measures included the Scale of Prodromal Symptoms. Clinical insight was measured using the Scale to Assess Unawareness of Mental Disorder, and changes in subjective experience were assessed using the Subjective Well-being Under Neuroleptics, Short version. The time frame was the first 8 weeks after beginning study medication. Thirty-six treatment-seeking prodromal patients (men, 42%; mean [SD] age, 23.4 [5.6] years) were enrolled. At the 12-week follow-up point, 30 participants (83%) remained in the trial. Improvements on the Scale of Prodromal Symptoms and Scale to Assess Unawareness of Mental Disorder scores were statistically significant at end point. Although the Subjective Well-being Under Neuroleptics, Short version total scores improved significantly at 4 weeks, however, they did not change significantly from baseline at 8 weeks. This trial suggests that aripiprazole not only produces a clinical benefit in prodromal subjects but also results in a high adherence to medication with immediate improvements in insight and subjective well-being. Although further placebo-controlled studies are needed, aripiprazole might be a first-line treatment for individuals at imminent risk for psychosis.